2020
DOI: 10.3390/w12041068
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ultrasound as an Advanced Oxidation Process for the Degradation of Emerging Pollutants in Water

Abstract: Emerging pollutants are compounds of increased environmental importance and, as such there is interest among researchers in the evaluation of their presence, continuity and elimination in different environmental matrices. The present work reviews the available scientific data on the degradation of emerging pollutants, mainly pharmaceuticals, through ultrasound, as an advanced oxidation process (AOP). This study analyzes the influence of several parameters, such as the nature of the pollutant, the ultrasonic fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(25 citation statements)
references
References 79 publications
(145 reference statements)
0
25
0
Order By: Relevance
“…Increasing solution temperature can increase pharmaceutical removal by reducing cavitation threshold and thus, increase HO • production [40] , [136] . That is, increasing solution temperature is expected to increase reaction rates, increasing removal rates of e.g.…”
Section: Ultrasound (Us) Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing solution temperature can increase pharmaceutical removal by reducing cavitation threshold and thus, increase HO • production [40] , [136] . That is, increasing solution temperature is expected to increase reaction rates, increasing removal rates of e.g.…”
Section: Ultrasound (Us) Processingmentioning
confidence: 99%
“…That is, increasing solution temperature is expected to increase reaction rates, increasing removal rates of e.g. DCF [118] , SMX and IBP [40] . However, Sutar et al [137] showed using DCF that there exists a temperature threshold of 50 °C, above which increasing solution temperature reduced the degradation efficiency from 100% to below 20%.…”
Section: Ultrasound (Us) Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique has attracted wide attention in water and sewage system due to simplicity, high decomposition speed, and zero secondary pollution. Ultrasound is evaluated as one of the AOP for the degradation of pollutants in the water system due to the formation of free hydroxyl radicals with oxidising capabilities [ 50 , 51 ]. Ultrasound technique was reported to disinfect microorganisms and viruses by several mechanisms based on acoustic cavitation [ 49 , 52 , 53 ].…”
Section: Virus Disinfection Via An Advanced Oxidation Processmentioning
confidence: 99%
“…It covers the main results and limitations of each method. Another review focused on the use of ultrasound as AOP 40. The authors analyze and discuss the potential risks and implications and also describe the associated economic costs and future prospects for using ultrasound to resolve/minimize water pollution by emerging pollutants.…”
Section: Introductionmentioning
confidence: 99%